Sphingomonas panacisoli sp. nov., bacterium isolated from soil in South Korea. Issue 3 (9th March 2021) - Maeng, Soohyun; Liu, Qingzhen; Park, Yuna; Bai, Jaewoo; Im, Wan-Taek
Abstract : A newly isolated bacterial strain designated as HKS19 was isolated from a ginseng cultivation soil sample collected in South Korea. Cells of the strain HKS19 were Gram-stain-negative, rod, oval-shaped and they formed yellow colonies when grown on R2A agar at 30 °C. HKS19 showed the highest 16S rRNA gene sequence similarity (98.6%) with Sphingomonas asaccharolytica NBRC 15499 T . Its growth was observed at 10–37 °C (optimum 30 °C), pH 6–9 (optimum pH 7), and in the presence of 0–1% NaCl (optimum 0%). The genome size of HKS19 was 3.4 Mb and the G+C content was 65.1 mol%. The main polar lipid of strain HKS19 was diphosphatidylglycerol (DPG), the predominant respiratory quinone was Q-10 and the major fatty acids were a summed feature 8 (C18 : 1 ω6 c / C18 : 1 ω7 c) and C16 : 0 . Based on the phylogenetic, genotypic, phenotypic and chemotaxonomic analysis, strain HKS19 represents a newly isolated species of the genus Sphingomonas, for which the name Sphingomonas panacisoli is proposed. The type strain is HKS19 T (=KACC 18881 T =LMG 29564 T ).